The Wardah Effect: Mengapa Produk Ini Menjadi Pilihan Utama - Faisa Maylani Saputri; Lutfia Nur Aini; Trianing Arofah; Ruth Natalia Susanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The purpose of this study is to assess the impact of halal brands, brand image, and price perceptions on the motivation and purchasing choices of Wardah consumers, as well as to identify the psychological and behavioral factors underlying the phenomenon of